Microscopic image and text examination of conventional and digital print-outs / Muhammad Yusuf Masod, Professor Madya Hamidin Abdullah and Ridzuan Ahmad @ Awang - Abdullah, Hamidin; Ahmad @ Awang, Ridzuan (Research Management Institute (RMI), 2014)
Wide spread of printers and computers have led to increasing use of print documents in people's common life. While mass print, automatic print quality evaluation is necessary in the fast print process to avoid the quality defect immediately when it appears. Also, in many cases print materials are direct accessories to many criminal and terrorist acts, for example forge contract, hence print identification has become more importance. With the technology that is evolving as rapidly as conventional and digital printing, however, it is easy to lose track of the many processes and the many variables in each process. Furthermore, as digital prints often appear similar to one another and to prints of traditional processes, comparing digital and conventional printouts can be confusing. This research aims to examine and characterizing digital and conventional printouts and investigate whether digital prints outs are significantly different than conventional printouts which can then be used for management and control purposes. Prior efforts to characterize digital and conventional printout have been made, however it is based on visual examination (Gascoigne 2004, Jarry 1996 and Lloyd and Taub 1988). To address this issues, In order to evaluate the print quality automatically or identify the source of the printouts intelligently, this study research will fully utilised primary examination of print with the naked eye, a magnified view of its edges and surface will render additional information. A stereomicroscope that magnifies up to approximately 20x to 50x as an instrumentation. The print identification checklist as proposed by Jurgens C. (2009) to keep track of the observations during identification. The experimental results are then presented and analyzed, showing that the results are promising and convinced.